PENERAPAN MODEL KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 169 PEKANBARU - Afriza Rahma Rani; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This research was conducted because of the result of learning social study class IV SD Negeri 169 Pekanbaru From 40 students who achieve KKM just 18 students (45%) while students who did’nt complete 22 students (55%) with an average of 65,3%. The purpose of this research to improve learning outcomes social sciences class IV SD Negeri 169 Pekanbaru with the application of learning models snowball throwing. The results obtained by the average value of 65,3 basic score increased in the first cycle of 22,12% to 79,75. In the second cycle the average value of students also increased by 25,75% to 82,12. Activities of teachers at the first meeting of 75% with both categories. The second meeting increased to 79,17% in both categories. In the second cycle increased to 83,3% with the category very well. At a meeting of the second meeting of the second cycle, the activities of teachers increased to 95,83% with the category very well. Activities of students in the first cycle of the first meeting activity students acquire a percentage of 62,5% in both categories. The second meeting of the first cycle to 75% in both categories. At the first meeting of the second cycle of student activity increased to 79,17% with the category very well, and at the second meeting of the second cycle increased again to 87,5% with the category very well.Key Word: Snowball Throwing, Learning outcomes social science.